Research Progress and Prospect of High-Nitrogen Austenitic Stainless Steel - Jiao Xiaofei, Li Qun, Wang Dongjia, Wang Shuhuan, Ni Guolong (Teshugang)
High-nitrogen austenitic stainless steels exhibit high strength and toughness， strong wear and corrosion resistance， and also possess non-magnetic property along with excellent biocompatibility. These attributes have garnered them extensive attention across a variety of fields， including ocean engineering， energy and chemical industries， national defense and aviation， and biomedical applications. However， in the preparation process， it still faces a series of problems and technical challenges such as inaccurate control of nitrogen enrichment levels， easy precipitation of nitrogen during solidification of high-nitrogen steels to form pores， and precipitation of coarse nitrides during hot working， which limits its large-scale development and application to a certain extent. The development status， preparation process， and strengthening mechanisms of high-nitrogen austenitic stainless steel have been systematically elaborated. Firstly， a review of the domestic and international development history and current research status of high-nitrogen austenitic stainless steel are reviewed. Secondly， the production and preparation processes for high-nitrogen austenitic stainless steel have been summarized， encapsulating various techniques for the melting-casting method. This includes a comparison and analysis of their advantages and disadvantages， such as the Larger Pool Method， Pressurized Induction Melting， Pressurized Ladle Blowing， Pressurized Electroslag Remelting， and Pressurized Plasma Arc Melting. Additionally， an overview of the powder metallurgy process for fabricating high nitrogen steel is presented， which includes methods such as Mechanical Alloying， Gas Atomization， Plasma Rotating Electrode Process， and Solid-state Powder Nitriding. Furthermore， a summary is provided around various forming processes including Hot Isostatic Pressing， Spark Plasma Sintering， Metal Injection Molding， Hot Pressing Sintering， Cold Pressing Forming， and Additive Manufacturing. Ultimately， the discourse delves into the mechanisms underlying nitrogen's fortification role in austenitic stainless steel， encompassing Solution Strengthening， Grain Refinement Strengthening， Strain Hardening， and Precipitation Hardening. Moreover， the dialogue addresses the predominant challenges encountered in the evolution of high nitrogen austenitic stainless steel， proffering a prospective outlook on the field's advancement.